JOGLOSEMAR WAYANG KULIT: A Study on the Symbols and Meaning of Wayang Kulit in Jogja, Solo, and Semarang - Kamsidjo Budi Utomo (Universal Journal, 2020)
The purpose of this research was to investigate the semiotic meaning of Wayang Gagrak in Jogjakarta, Surakarta, and Semarang. It was also intended to examine the functions and indigenous elements of Wayang Kulit in those areas. This research employed a qualitative method to explore the issue in a flexible manner but at the same time, retaining an in-depth and accurate result. Peirce‟s semiotic analysis, comprising three elements, i.e., representamen, object, and interpretant, was used to scrutinize Wayang Gagrak from the three provinces mentioned previously. Representamen refers to everything that can function as a sign. The term object, in this context, refers to the component represented by the sign, while the interpretant is the interpretation of the sign. All data from the observation of Wayang Gagrak of the three areas, literature related to Peirce‟s semiotic analysis, and interview with informants (such as dalang or puppeteer, semiotic experts, and Wayang enthusiasts) were examined to present a thorough result. The criteria of this objective involve: (1) able to explore all details and signs represented visually in Wayang Gagrak of the selected areas; (2) able to present the meanings of the symbols of the Wayang, and; (3) able to examine the functions of the signs.